Spawn Timing and Redd Morphology of Anadromous Coastal Cutthroat Trout Oncorhynchus clarkii clarkii in a Tributary of South Puget Sound, Washington. (31st March 2016) - Losee, James P.; Phillips, Larry; Young, William C.
Abstract: Spawn timing information for Coastal Cutthroat Trout Oncorhynchus clarkii clarkii is typically limited to counts of adult fish at traps and tagging studies based on few samples. These types of data have suggested a protracted spawning period that occurs between November and March. We sought to determine the spawn timing and describe the redd morphology of anadromous Coastal Cutthroat Trout in a typical coastal stream of southern Puget Sound, Washington. Skookum Creek was surveyed for live and dead Coastal Cutthroat Trout and redds once weekly from early October to early June during six spawning season (2008–2014). In total, 148 live adults and 544 redds were observed. The timing of redd construction was highly variable among years, with 50% of redd detections occurring by as early as February 13 or as late as April 27. Measurements were collected from individual redds to describe redd morphology and the habitat type utilized by spawning Coastal Cutthroat Trout. Redds were typically found in substrate composed of small gravel (1.3–3.8 cm) and large gravel (3.8–7.6 cm) and in water with an average velocity of 0.60 m/s. The pit within redds averaged 0.43 m wide × 0.48 m long. Information from this study may provide new insights that will allow fisheries managers to begin developing a species‐specific approach to monitoring anadromous Coastal Cutthroat Trout. Received July 2, 2015; accepted December 2, 2015 Published online March 31, 2016